2014
DOI: 10.1002/jmrs.58
|View full text |Cite
|
Sign up to set email alerts
|

Definition and visualisation of regions of interest in post‐prostatectomy image‐guided intensity modulated radiotherapy

Abstract: IntroductionStandard post-prostatectomy radiotherapy (PPRT) image verification uses bony anatomy alignment. However, the prostate bed (PB) moves independently of bony anatomy. Cone beam computed tomography (CBCT) can be used to soft tissue match, so radiation therapists (RTs) must understand pelvic anatomy and PPRT clinical target volumes (CTV). The aims of this study are to define regions of interest (ROI) to be used in soft tissue matching image guidance and determine their visibility on planning CT (PCT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This might increase the time required to treat each patient, at least during the initial implementation phase. Radiation Therapist training would also be necessary, but they have been shown to be adept after using a locally produced image atlas [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might increase the time required to treat each patient, at least during the initial implementation phase. Radiation Therapist training would also be necessary, but they have been shown to be adept after using a locally produced image atlas [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Departments also should ensure that the image quality of their CBCT scans is adequate for soft tissue matching. Structure identification on CBCT scans was assessed at NSCC and it was found that with training, the anterior rectal wall, posterior bladder wall and prostate bed surgical changes were well recognised on the majority of scans [ 14 ].…”
Section: Resultsmentioning
confidence: 99%